Effectiveness of a Public Health Campaign in Raising Awareness of Balanced Nutrition in Primary School Children - Resty Noflidaputri; Wijianto; Kalasta Ayunda Putri; Dika Betaditya; Wahyu Vera Wardani (Miracle Journal Get Press, 2025)
This study used a quantitative approach with a quasi-experimental research design to measure the effectiveness of a public health campaign in improving balanced nutrition awareness in primary school children. Data were collected through pre-test and post-test using a structured questionnaire that had been tested for validity and reliability. The results of the analysis showed a significant increase in the average score of students' knowledge from 65.20  7.80 before the intervention to 88.60  5.20 after the health campaign (p=0.001), as well as students' awareness which increased from 60.30  6.70 to 85.50. This study provides empirical evidence that well-designed nutrition education can be a solution to address nutritional problems in children, such as malnutrition and obesity, thereby supporting the creation of healthier and more productive generation in the future.